2015
DOI: 10.1016/j.ijrobp.2014.08.353
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Toxicity After Proton Therapy For Prostate Cancer: An Analysis of Outcomes of Prospective Studies Conducted at the University of Florida Proton Therapy Institute

Abstract: PT was associated with a low rate of GR2+ gastrointestinal toxicity, predominantly transient RB, which was highly correlated with anticoagulation and rectal DVH parameters. Techniques that limit rectal exposure should be used when possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
1
44
1
Order By: Relevance
“…Interestingly, acute grade 1 GI toxicity was associated with several low-intermediate rectal dose parameters including rectal minimum and median doses, V10 and V20, infield rectal minimum dose, V10, V20, and ARW median dose, V10 through V65 at all dose levels tested (Figure 4). A report of over 1500 prostate cancer patients treated with PT in the intact setting found that all dosimetric parameters for the rectum and rectal wall were highly correlated with the risk of grade 2 rectal bleeding [32], and break points best dichotomizing this risk were rectal V30 < 26.4% and V75 < 9.4% and rectal wall V30 < 27.7% and V75 < 9.2%. In our series of prostate cancer IMRT in the intact setting, infield rectum mean/ median doses, V30, and V40 were similarly associated with GI grade 2 toxicity [21].…”
Section: Toxicity Associationsmentioning
confidence: 99%
“…Interestingly, acute grade 1 GI toxicity was associated with several low-intermediate rectal dose parameters including rectal minimum and median doses, V10 and V20, infield rectal minimum dose, V10, V20, and ARW median dose, V10 through V65 at all dose levels tested (Figure 4). A report of over 1500 prostate cancer patients treated with PT in the intact setting found that all dosimetric parameters for the rectum and rectal wall were highly correlated with the risk of grade 2 rectal bleeding [32], and break points best dichotomizing this risk were rectal V30 < 26.4% and V75 < 9.4% and rectal wall V30 < 27.7% and V75 < 9.2%. In our series of prostate cancer IMRT in the intact setting, infield rectum mean/ median doses, V30, and V40 were similarly associated with GI grade 2 toxicity [21].…”
Section: Toxicity Associationsmentioning
confidence: 99%
“…However, this might give relatively high doses to organs such as the femur/femoral heads, or in some cases, the target or normal tissue constraints cannot be fulfilled. Oblique lateral fields may therefore be applied as in the study of Colaco et al [8], where beam angles up to ±11 off the lateral opposing field configuration were used. Using anterior or posterior oblique (AO/PO) lateral fields, the distal ends of the SOBP will be directed more toward or extend into organs at risk (OARs), such as the rectum or bladder.…”
Section: Introductionmentioning
confidence: 99%
“…With the caveat that enrollment criteria were more stringent on the AHPT trial (IPSS of 15; no use of alpha-blockers; no diabetes mellitus; no prior intrapelvic surgery; no current or continuing use of anticoagulation, and no saw palmetto or immunosuppressants), the rates of freedom from progression and toxicity have been similar to those achieved with standard fractionated proton therapy at the same institution [6,22,23]. The 5-year rates of freedom from biochemical progression for low-and intermediate-risk patients of 98.3% and 92.7% were comparable to rates achieved on prospective clinical trials of standard fractionated proton therapy using similar treatment techniques for low-and intermediate-risk disease (99% and 99%) [6].…”
Section: Discussionmentioning
confidence: 93%